Analysis of risk factors for persistent infection of asymptomatic women with high-risk human papilloma virus - Nianmin Shi; Qiang Lu; Jiao Zhang; Li Li; Junnan Zhang; Fanglei Zhang; Yanhong Dong; Xinyue Zhang; Zheng Zhang; Wenhui Gao (Taylor & Francis Group, 2017)
Objective: This study aims to prevent persistentinfection, reduce the incidence of cervical cancer, and improve women's health by understanding the theoretical basis of the risk factors for continuous infection of asymptomatic women with high-risk human papilloma virus (HPV) strains via information collected, which includes the persistent infection rate and the most prevalent HPV strain types of high risk to asymptomatic women in the high-risk area of cervical cancer in Linfen, Shanxi Province. Methods: Based on the method of cluster sampling, locations were chosen from the industrial county and agricultural county of Linfen, Shanxi Province, namely the Xiangfen and Quwo counties. Use of the convenience sampling (CS) method enables the identification of women who have sex but without symptoms of abnormal cervix for analyzing risk factors of HPV-DNA detection and performing a retrospective questionnaire survey in these 2 counties. Firstly, cervical exfoliated cell samples were collected for thin-layer liquid-based cytology test (TCT), and simultaneously testing high-risk type HPV DNA, then samples with positive testing results were retested to identify the infected HPV types. The 6-month period of testing was done to derive the 6-month persistent infection rate. The retrospective survey included concepts addressed in the questionnaire: basic situation of the research objects, menstrual history, marital status, pregnancy history, sexual habits and other aspects. The questionnaire was divided into a case group and a comparison group, which are based on the high-risk HPV-DNA testing result to ascertain whether or not there is persistent infection. Statistical analysis employed Epidate3.1 software for date entry, SPSS17.0 for date statistical analysis. Select statistic charts, Chi-Square Analysis, single-factor analysis and multivariate Logistic regression analysis to analyze the protective factors and risk factors of high-risk HPV infection. Risk factors are predicted by using the classification tree. Results: 3000 women participated in the study. The high-risk type HPV infection rate was 8.7%, the persistent infection rate was 7.5%. The persistent infection rates for the 2 age groups (ages 18-26 and 27-30) were 6.9% and 8.7%. The persistent infection rates of Xiangfen county were 7.4% and 7.4% respectively, and those of Quwo county were 7.8% and 11.6% respectively; there was no significant difference between each pair of groups. Single risk-factor analysis showed that first-time sex at age under 20, high school/technical secondary school education or above, multiple sexual partners, having more than 2 sexual partners in the past 6 months, oral sex, and colitis are the risk factors of high-risk type HPV infection. Multivariate analysis showed that the number of sexual partners, smoking and oral sex had an effect on HPV infection. The risk of HPV infection from smoking was 5.0-fold higher, and the risk of HPV infection from oral sex was 6.1-fold higher. Having more than 2 sexual partners increase the risk of HPV infection. By the predicated model analysis, the probability of HPV conveyed by oral sex was 14.8%; if the sexual companion number was zero or more than 2 without oral sex, the probability of HPV infection was 12.1%; if there was one sexual partner who smokes without oral sex, the probability of infection was 18.6%; if there was one sexual partner who does not smoke and without oral sex, the probability of infection was 3.6%. Conclusion: The persistent infection rate of asymptomatic women for high-risk type HPV is lower than those women in all ages. High-risk type HPV infection risk factors include the number of sexual partners, oral sex and smoking. Thus, young women may be able to reduce the risk of infection with high-risk type HPV by reducing the number of sexual partners, forming a correct sexual life habit, and avoiding smoking.